2016
DOI: 10.1007/s10578-016-0671-2
|View full text |Cite
|
Sign up to set email alerts
|

Parental Involvement in Cognitive Behavior Therapy for Children with Anxiety Disorders: 3-Year Follow-Up

Abstract: Parental factors have been linked to childhood anxiety, hence, parental involvement in cognitive behavioral therapy (CBT) for anxious children has been examined. However, findings do not consistently show added effects of parent-enhanced CBT, longitudinal investigations are scarce and long-term effects unclear. In the present study, 40 out of 54 families who, 3 years previously, completed one of two types of CBT treatment: with limited or active parental involvement, were assessed using semi-structured diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
0
11
1
Order By: Relevance
“…However, receiving professional support alongside computerized therapies might be beneficial, such that blended approaches could be optimal [ 57 ]. In addition, parental involvement in child CBT may lead to better outcomes, although evidence on their role in adolescent CBT is less conclusive [ 58 , 59 ]. Few of the studies we identified described direct parental involvement in the cCBT intervention; for those that did, the extent of parental involvement was minimal and sometimes optional.…”
Section: Discussionmentioning
confidence: 99%
“…However, receiving professional support alongside computerized therapies might be beneficial, such that blended approaches could be optimal [ 57 ]. In addition, parental involvement in child CBT may lead to better outcomes, although evidence on their role in adolescent CBT is less conclusive [ 58 , 59 ]. Few of the studies we identified described direct parental involvement in the cCBT intervention; for those that did, the extent of parental involvement was minimal and sometimes optional.…”
Section: Discussionmentioning
confidence: 99%
“…This suggestion remains only speculative however, and needs to be tested in empirical trials. Indeed, evidence from clinic-delivered CBT has produced conflicting findings with respect to the value of parental involvement in therapy (Walczak et al, 2017; Breinholst et al, 2011). Manassis et al (2014) suggested that this variation in findings may reflect the different ways in which parents can be involved in treatment, and highlighted the need for research to identify specific parental behaviours that enhance treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, among youth participants who received CBT+P, the specific parent condition (RLST or RFST) did not significantly predict whether youth met diagnostic criteria for their targeted primary anxiety disorder or any anxiety disorder at follow-up. The absence of differences between treatment conditions in the present study is consistent with findings of some past follow-up studies that involved parents in treatment of youth anxiety disorders (Barrett et al, 2001), but inconsistent with other studies (Cobham et al, 2010;Walczak et al, 2016) that found superior diagnostic outcome at follow-up in parent-involved conditions compared with youth ICBT. While the Cobham study focused on parental anxiety as a parent factor to target during treatment, the Walczak study is most similar to the current study as it targeted specific parenting behaviors and included contingency management and transfer of control strategies in the active parent condition (similar to RFST condition).…”
Section: Primary Anxiety Outcomescontrasting
confidence: 54%